Quality assessment of “naturally occurring” high-percentage L-dopa commercial products proposed as dietary supplements on the Internet: from labeling to analytical findings - Aureli, Federica; Gaudiano, Maria Cristina; Raimondo, Mariangela; Maccelli, Alessandro; Di Giorgio, Domenico; Gramazio, Marta; Borioni, Anna; Bartolomei, Monica (Frontiers in Chemistry, 2025)
IntroductionLevodopa (L-dihydroxyphenylalanine or L-dopa) is a precursor of the neurotransmitter dopamine and is used in Parkinson’s disease therapy. L-dopa dietary supplements are widely marketed as brain support. Among the L-dopa products claiming to contain botanical extracts, those from Mucuna pruriens are the most frequently offered on the Internet. The natural percentage of L-dopa in M. pruriens seeds or leaves varies from 1% to 7%, but extracts standardized at higher percentages of L-dopa are also available.MethodsFour L-dopa products marketed as dietary supplements were purchased online and analyzed for labeling accuracy. The identification of L-dopa and the detection of undeclared pharmaceutical or nootropic ingredients were carried out via mass spectrometry (LC-MS Q-TOF). Nuclear magnetic resonance (NMR) spectroscopy was used to confirm the presence of L-dopa and quantify it. Furthermore, a Google Trends analysis was conducted to study interest in the terms “levodopa” and “brain supplements” and their Italian equivalents, over the last 10 years in Italy and globally.ResultsVisual inspection of labeling revealed that the extract of M. pruriens, which is not allowed in dietary supplements in Italy, was listed on three products, while the extract of Vicia faba was declared in one sample. Some labeling concerning the dosage of L-dopa was ambiguous. LC-MS and NMR analyses confirmed the presence of L-dopa in all the samples. No undeclared active pharmaceutical or nootropic ingredients were detected. The amount of L-dopa in the capsules was found to match the labeled dosage in some samples, but others were either overdosed or underdosed. Trend analysis indicated increasing interest in the terms “levodopa” and “brain supplements” both in Italy and worldwide.DiscussionThe obtained results showed evidence of potential risks related to consuming dietary supplements purchased online containing high-dose L-dopa. These risks arise from the inclusion of unauthorized botanical extracts, unclear labeling, and inconsistencies between labeled and actual dosages. Given the observed increasing public interest in levodopa, these findings highlight the need to control this market and inform consumers and physicians about the risks of purchasing unauthorized online products.